ANALISIS STRATEGI PEMASARAN PRODUK METCOVAZIN PADA KLINIK LAMPUNG WOUND CARE SEMASA PANDEMI COVID-19 - Hepiana Patmarina; Ramadhani Wulandari; Farida Efriyanti (Jurnal Manajemen dan Bisnis (JMB), 2023)
ABSTRACT In instances and generation of globalization, wound health clinics, particularly current health clinics, has grow to be the simple demand for diverse wound health merchandise, that may meet the modern-day marketplace percentage. consequently, the researchers conducted the studies at one of the wound health clinics in Bandar Lampung, particularly Lampung Wound Care hospital, positioned on Jl. Ra Basyid Labuan Dalam wishes to recognize the Metcovazin product income figures and profits degree within the previous couple of semesters. Some stage in the developing enterprise of Lampung Wound Care sanatorium underneath development, 2020 became an international pandemic that led to all sectors of the economy being hampered. With the WHO declaration, Covid-19 has grow to be a global pandemic, client conduct in all enterprise sectors is professional. So the rampant outbreak of Covid-19 is having an effect on commercial enterprise in Indonesia. The strategic making plans in every health facility should be deliberate in addition to feasible to count on the advent of different competitors. That is finished whilst the health center determines the first-class attempt to overcome different competition, due to the fact within the commercial enterprise or business global, advertising is one of the major factors to growth income. Keywords: Marketing Strategy, Sales Volume, Lampung Wound Care Clinic